Climate Change Adaptation Strategies Employed By Rural Women Farmers In The Upper West Region Of Ghana: Implications On Wellbeing - Afful, R. (University of Ghana, 2020)
There is increased investment and adoption of adaptation strategies by rural women farmers to reduce vulnerabilities. Studies have shown that most of the adaptation options provided by key district adaptation stakeholders do not address the wellbeing needs of rural women farmers. This research is an effort to substantially incorporate considerations of human wellbeing into how adaptation interventions are comprehended. It therefore employed the wellbeing framework (material, relational and life satisfaction) to unpack some key elements that drive the choices and actions of rural women farmers in adapting to climate variability/change and adaptation options likely to improve wellbeing. A mixed method approach was employed (involving, Focus Group Discussions, community profiling, key informant interview and review of secondary information). Ranking by the Kendall’s Coefficient of Concordance revealed that majority of the women farmers employ sustainable land management practices (improved seed variety, mix cropping/legume cropping and changing planting dates) in addressing climate variability/change. The probit linear regression model revealed that factors that affect rural women farmers’ choice of adaptation options are age, membership of a farmerbased organisation, farm size and household size. From the ordered logit model, the number of years lived in a community and ownership of a television set by a woman farm is significant to their material wellbeing. Size of household, ownership of a gas/kerosene stove were also considered important to enhancing the relational wellbeing of rural women farmers. Additionally, years of farming/farming experience, anti-erosion measures and improved crop varieties were identified as very important to life satisfaction wellbeing of rural women farmers. The results highlight the need for increased understanding of the critical constituent of individual and household wellbeing needs to ensure the provision of equitable, more effective and sustainable adaptation options for improved resilience.
PhD. Environmental Science
Keywords: Climate Change; Women Farmers; Upper West Region; Ghana